Beyond 4 × 100 Gbps Optical Backhaul Network With DSP Assistance Based Nonlinear Impairments Mitigation. Issue 10 (5th October 2021) - Ali, Farman; Armghan, Ammar; Muhammad, Fazal; Habib, Usman; Ali, Asar; Qamar, Muhamamd Salman; Ali, Usman; Khan, Maqsood Ahmad
Abstract: Backhaul networking is the highlighted objective of today telecommunication structure. Additionally, the backhaul networking can be possible easily utilizing optical fiber networks (OFNs). This paper studies 4 × 100 Gbps framework of long haul capacity wavelength division multiplexing (WDM) system, taking into account the impairments of nonlinearities, amplified spontaneous emission (ASE) fiber dispersion. Digital signal processing based receiver is proposed to maintain performance of OFNs in presence of nonlinear issues. The complete procedure of proposed WDM based OFNs is verified theoretically. The simulation analysis proved the validation of presented model against nonlinear impairments and provides 2.1 × 10 − 6 bit error rate (BER) at 25 and 50 GHz channel spacing, 90 μm 2 effective area and 500 km transmission length. Key Points: Mitigation of nonlinearities in long haul high capacity optical networks Nonlinear issues Digital signal processing for long haul optical communication